2019
DOI: 10.25182/jgp.2019.14.3.149-156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Torbangun Leaves(Coleus amboinicus Lour) Extract on Blood Glucose and Super Oxide Dismutase Activity in Hyperglycemic Rats

Abstract: This research aimed to analyze the yield of torbangun extract, flavonoid content, and antioxidant activity of TE-S and its effect on the activity of SOD enzymes and blood glucose level in hyperglycemic rats as a DM animal model. The water content of simplicia was measured by the gravimetric method. The antioxidant activity of TE-S was determined using the DPPH method, while the total flavonoid was measured using spectrophotometry. The study was a completely randomized design using 25 Sprague Dawley rats. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The difference in the higher IC50 content (126.4216 mg/L) means it has a lower antioxidant capacity in this study did not give a significant difference in results. Meanwhile, based on the results of this study, Similar to the study conducted by Andrestian et al (2019), in diabetic rats (streptozotocin 40 mg/kgBW) given torbangun leaf extract with an IC50 of 306.28 ppm can increase SOD levels but not significantly for 14 days. Similar to the study conducted by Luandayanti (2013), in diabetic rats induced with streptozotocin 100 mg/kgBW and given mahogany seed methanol extract (IC50 117.73 mg/L) there was an increase in SOD levels but not significant.…”
Section: Effect Of Taro Leaf Extract On Sod and Crp Levelssupporting
confidence: 75%
“…The difference in the higher IC50 content (126.4216 mg/L) means it has a lower antioxidant capacity in this study did not give a significant difference in results. Meanwhile, based on the results of this study, Similar to the study conducted by Andrestian et al (2019), in diabetic rats (streptozotocin 40 mg/kgBW) given torbangun leaf extract with an IC50 of 306.28 ppm can increase SOD levels but not significantly for 14 days. Similar to the study conducted by Luandayanti (2013), in diabetic rats induced with streptozotocin 100 mg/kgBW and given mahogany seed methanol extract (IC50 117.73 mg/L) there was an increase in SOD levels but not significant.…”
Section: Effect Of Taro Leaf Extract On Sod and Crp Levelssupporting
confidence: 75%
“…The improved antioxidant enzyme activities demonstrated by the PRF-CS indicated that this fraction might prevent enzymes from glycating or decrease reactive oxygen free radicals and enhance the antioxidant enzyme's activities. The observation demonstrated the free radicals scavenging activity abilities of the PRF-CS, exerting an advantageous action through protection against pathogenic changes generated by superoxide radicals and H2O2 radicals (Andrestian et al 2019). The PRF-CS activities observed might be due to the phenolic compounds.…”
Section: Effect Of Prf-cs On Oxidative Stress Markersmentioning
confidence: 76%
“…The treatment group given the purple okra supplement with a quercetin content of 18.65 mg per day showed a decrease in SOD levels of 0.15±0.17 U/mL after the intervention. SOD activity was used as one of the parameters in determining the presence of antioxidant activity (Andrestian et al 2019). The decrease in SOD levels of the subjects given the purple okra supplement can be explained by the role of the supplement in balancing the oxidative stress caused by free radicals.…”
Section: Changes In Superoxide Dismutase Levelsmentioning
confidence: 99%